Pendekatan Pembentukan Perilaku Keagamaan Siswa Melalui Tata Tertib - Lonika, Tasya Bebi; Rahmah, Eka Naelia (Prodi Pendidikan Keagamaan Islam, 2023)
In this modern era, students' religious behavior has decreased such as their religious activities, morals, and ways of looking. School rules based on religious values are one of the efforts in shaping students' religious behavior. The purpose of this study was to find out how to approach the formation of students' religious behavior through school rules. The research method used is descriptive qualitative, data collection using observation, interview, and documentation methods. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study show that the approach to shaping students' religious behavior through school rules at SMP IT Cahaya Islam Buaran South Tangerang works well by providing experiences such as manners, obligatory congregational prayers and sunnah. Habituation to perform obligations repeatedly. Provide examples such as obeying prayers, dressing, and manners. Emotional approach with religious studies. Rational approach with understanding through tausiyah. A functional approach with examples, direction, and knowledge. This approach is applied through school rules in the form of obligations, prohibitions and sanctions.